Efforts in Improving Teachersâ Competencies Through Collaboration between Teacher Forum on Subject Matter (MGMP) and Pre-Service Teacher Training Institution (LPTK) - Purwoko, A. A.; Andayani, Y.; Muntar, M.; Diartha, I. N. (Jurnal Pendidikan IPA Indonesia, 2017)
The goal of this study is to improve high school chemistry teacherâs competency in terms of classroom instruction. This goal is achieved through the workshop and continuous assistance activities that enable teachers to improve their knowledge and skills in developing learning scenarios that reflect scientific methods (brain-based learning) in the classroom instruction. The effect of teachersâ competence improvement was measured by a survey of studentâs perception on the classroom teaching-learning process, using Likert-scale questionnaire. The first poll was conducted before the program was started, and the second one was after the program completion. The first observation shows that only 18% of students perceive that the chemistry learning process in the classroom are âgood,â while the rest (82%) say that it is âfairâ. However, the second poll shows that there are 45% of students who perceive that the learning process is âgoodâ; interestingly, there are 35%, and 20% of respondents say âexcellentâ and âfair,â respectively. Furthermore, data analyses using chi-square test conclude that the continuous teacher assistance activity significantly improves teachersâ competencies. This article describes detailed of collaboration program and the results of improvement of chemistry teachersâ competence in north Lombok regency.